Internal governance, legal institutions and bank loan contracting around the world - Ge, Wenxia; Kim, Jeong-Bon; Song, Byron Y. (Journal of Corporate Finance, 2012)
Using a sample of non-U.S. firms from 22 countries during 2003–2007, we examine the effect of firm-level governance on various features of loan contracting in the international loan market. We find that banks charge lower loan rates, offer larger and longer-maturity loans, and impose fewer restrictive covenants to better-governed firms. We also find that the favorable effect of firm-level governance on some loan contracting terms is stronger in countries with strong legal institutions than in countries with weak legal institutions. Our results suggest that banks view a borrower's internal governance as a factor that mitigates agency and information risk, and that country-level legal institutions and firm-level governance mechanisms complement each other in influencing loan contracting terms.